RNA as an Emergent Entity: An Understanding Gained Through Studying its Nonfunctional Alternatives - Krishnamurthy, Ramanarayanan (Synlett, 2014)
RNA is arguably the most central member of the class of biomolecules in the extant biochemistry of the earth and, in a number of theories, is postulated to have played a key role in the origin of life. The most prominent among these theories is the ‘RNA world’ theory, which hypothesizes that RNA functioned both as the carrier of information and as a catalyst in many reactions. With new functions of RNA being discovered almost daily, there is much to learn about the operational versatility of this biopolymer. The past–present–future omnipresence of RNA has made it a molecule of intense scrutiny from the perspectives of structure, function, and applications. In this article, I present an understanding of the nuanced interrelationship between the structural components of RNA, and its propensity to undergo self-assembly, an understanding that was not gained by studying RNA, but rather was gained through a comparative study of its nonfunctional alternatives. The results from these juxtapositional studies suggest that RNA might be considered as an emergent structural entity and as a product of chemical evolution.1 Introduction2 isoGNA: An Isomer of a Glycerol-Derived Acyclic Nucleic Acid3 Pentulose Nucleic Acids4 The Role of the Pent(ul)ofuranosyl Moiety: The ‘A-ha’ Moment5 Conclusion
Keywords: chemical evolution; DNA; oligonucleotides; RNA; self-assembly